2015
DOI: 10.1007/s11738-015-1895-7
|View full text |Cite
|
Sign up to set email alerts
|

Enterobacter sp. SE992-induced regulation of amino acids, sugars, and hormones in cucumber plants improves salt tolerance

Abstract: The rhizosphere of plants serves as a host for a number of microbiota. The mutualistic interaction between rhizosphere bacteria and plants supports the promotion of plant growth. These interactions also support responses against biotic and abiotic stresses through the modulation of plant metabolism. In the current study, we sought to investigate the effects of individual sugar, amino acid, and salicylic acid content upon cucumber plant salt tolerance with respect to Enterobacter sp. SE992 interactions. Enterob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…The endophytic strain, when applied to tomato plants, significantly increased the plant growth and development and confirmed our findings. The plant growth enhancing potential, in terms of shoot and root length, fresh and dry biomass, and chlorophyll contents, were in line with Khan et al [20], Ullah et al [33], Kang et al [19], Wahyudi et al [34], and Spaepen et al [29]. It is now known that IAA can be produced by variety of endophytes [20].…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…The endophytic strain, when applied to tomato plants, significantly increased the plant growth and development and confirmed our findings. The plant growth enhancing potential, in terms of shoot and root length, fresh and dry biomass, and chlorophyll contents, were in line with Khan et al [20], Ullah et al [33], Kang et al [19], Wahyudi et al [34], and Spaepen et al [29]. It is now known that IAA can be produced by variety of endophytes [20].…”
Section: Discussionsupporting
confidence: 81%
“…To date, numerous studies have investigated using plant growth promoting rhizobacteria (PGPRs) to mitigate the adverse effects of stresses on crops [9,10,18,19,25,28]. Such endophytic bacteria colonize healthy plant tissues without causing any disease symptoms to the host plants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the IAA secreting Enterbacter sp. SE992 induced amino acids, sugars and hormonal regulation in cucumber helped to enhance the salt tolerance of plants [29]. Very few studies were reported the PGPR-induced changes on amino acids in crop.…”
mentioning
confidence: 99%